Substituted 2-Aminotetrahydronaphthalenes as Affinity and Photoaffinity Probes for Dopamine Receptors - Ross, Nichiel Gregory (My University, 1990)
In the current investigation several biochemical techniques, including solubilization, affinity chromatography and photoaffinity labelling, were used to purify the D-1 dopamine agonist ADTN (2-amino-5, 6-dihydroxy-tetrahydornaphthealene) to be used as affinity and photoaffinity probes was an integral part of this investigation.
Solubilization of the D-1 receptor was achieved with several detergents although cholic acid proved to be the most effective for receptor solubilization prior to affinity chromatography. Using this procedure, yields of solubilized receptors of greater than 30% were consistently obtained.
An affinity chromatography protocol utilizing an ADTN analogue covalently coupled to an affinity matrix was established for cholate-solubilized D-1 receptor. The affinity protocol developed during this investigation purified the D-1 receptor approximately 50-fold, while an average of 8% of the receptors were recovered. These results were superior to any previous literature reports of D-1 receptor purification.
Several photoactive compounds were synthesized and used to crosslink D-1 receptors. One compound in particular, a photoactive derivative of the dopamine against ADRN, proved to be a useful ligand for this purpose. A tritiated derivative of this compound was covalently and specifically incorporated into a protein of M.W. =79kDa. This was the first report that the D-1 receptor had a M.W. of greater than 70kDa as determined by affinity crosslinking. Several other investigators have subsequently confirmed this observation.
Other photoactive compounds radiolablled with 125I were synthesized and examined for activity as D-1 and D-2 receptor probes. These compounds were not as useful as photoaffinity labels for dopamine receptors as had been originally proposed. The compounds did label a 50kDa protein which was determined to be neither the D-1 nor D-2 receptor. This protein (originally designated Apo-50 and later CatNAP) has very interesting properties as it possesses binding activities with several catecholamines which are without precedent in the literature.
Keywords: Neurology; Neurology